2018
DOI: 10.4067/s0034-98872018000600708
|View full text |Cite
|
Sign up to set email alerts
|

Experiencia en el tratamiento endovascular del accidente cerebrovascular isquémico agudo en un centro chileno

Abstract: The clinical improvement of these patients 24 hours after the procedure and at discharge demonstrate the effectiveness of endovascular treatment in ischemic stroke. The presence neurologists able to interpret multimodal images at the emergency room, the use of local guidelines, the availability of an experienced neuro-interventional team engaged with the workflow and the use of stent retrievers are strongly associated with good outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 25 publications
(35 reference statements)
0
2
0
5
Order By: Relevance
“…However, there is still a large gap in the availability of MT for the remaining 75% of the population who depend on the public healthcare system. We showed in a recent publication good results in MT for AIS in a single private stroke center in Santiago - Chile, 15 which encouraged us to start a pilot program in 2017 to reduce the breach of stroke care standards between private and public healthcare and to increasingly provide a timely and effective treatment for as many patients as possible.…”
Section: Discussionmentioning
confidence: 94%
“…However, there is still a large gap in the availability of MT for the remaining 75% of the population who depend on the public healthcare system. We showed in a recent publication good results in MT for AIS in a single private stroke center in Santiago - Chile, 15 which encouraged us to start a pilot program in 2017 to reduce the breach of stroke care standards between private and public healthcare and to increasingly provide a timely and effective treatment for as many patients as possible.…”
Section: Discussionmentioning
confidence: 94%
“…Varios estudios demuestran que los tratamientos tienen mayor eficacia si se aplican durante la ventana terapéutica; en el caso de la trombólisis endovenosa, la aplicación del fármaco Alteplasa dentro de las 4 -5 horas posteriores al evento, ha evidenciado menor número de complicaciones y rápida recuperación. Mientras que, en la trombectomía mecánica, la ejecución de este procedimiento se lleva a cabo en pacientes en estado crítico, con un cuadro clínico de más de 5 horas de evolución, sin embargo, debido al manejo tardío, los pacientes sometidos a este procedimiento requieren terapias de rehabilitación para recuperar sus funciones motoras (Vamsi et al, 2018;Reyes et al, 2018).…”
Section: Resultados Y Discusiónunclassified
“…Por otro lado, un tratamiento complementario es la trombólisis mecánica, la cual se emplea para eliminar los coágulos resistentes mediante dispositivos mecánicos como los stents autoexpandibles, con el fin de restablecer el flujo sanguíneo del tejido cerebral; dicho procedimiento está indicado en pacientes que poseen un vaso sanguíneo grande ocluido y con un intervalo de 6 -12 horas de evolución desde el inicio de los síntomas (Nogueira et al, 2018). Sin embargo, Reyes et al (2018) menciona que ''este procedimiento está contraindicado en pacientes con evidencia de infarto extenso, antecedentes de coagulopatía, hiperglicemia y alto riesgo de hemorragia sistémica''. En la Tabla 3 se describen las principales actividades que realiza el personal de enfermería, posterior a este procedimiento.…”
Section: Elaborado Por: Autoresunclassified
“…Many studies have reported the benefit of dual anti platelet therapy such as aspirin and clopidogrel in lowering the risk of stroke risk in patients with intracranial atherosclerosis. Surgical management of critical intracranial atherosclerosis may consist of measures such as extra-cranial to intracranial bye-pass grafting, endovascular treatment such as percutaneous trans-luminal angioplasty and stenting 5 . In patients with any degree of intracranial atherosclerosis the essence of management lies in the early diagnosis, identification of risk factors and their modification and drug therapy in patients diagnosed to be having significant atherosclerosis on the basis of imaging.…”
Section: Introductionmentioning
confidence: 99%